Inhibition of Streptococcus pneumoniae hyaluronidase by honeys of Malaysian origins (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2020)
Streptococcus pneumoniae, a major human pathogen causing meningitis, pneumonia and bacteraemia produce hyaluronidase as its virulence factor. This enzyme increase bacterial permeability to the host tissue by degrading hyaluronic acids that maintain the viscosity of connective tissues. Limited hyaluronidase inhibitor are available at the moment, thus lead us to identify potential hyaluronidase inhibitor from local products which is honeys. Three local honeys (Tualang, Kelulut and Gelam) have been selected and undergo hyaluronidase inhibition test through hyaluronic acids turbidity reduction assay. Honeys that show highest and lowest anti-hyaluronidase were analysed for flavonoid and phenolic content, to identify association between the contents and hyaluronidase inhibition rate. All honeys showed various degrees of inhibition against hyaluronidase of S. pneumoniae where honey with the highest anti-hyaluronidase activity is Kelulut with 18% inhibition  while honey with the lowest anti-hyaluronidase activity is Gelam with 2% inhibition. Kelulut also demonstrated highest phenolic content, where significant association was found between the inhibition and the content. Therefore, this study supported the claim that higher phenolic contents indicate greater inhibitory activity on hyaluronidase enzyme. The findings suggest that local Malaysian honey have potential as hyaluronidase inhibitor which could be beneficial for future treatment against S. pneumoniae infections.
Keywords: Streptococcus pneumoniae, hyaluronidase, inhibition, Kelulut, Gelam, Tualang, phenolic content, flavonoid